Self-care competence in the administration of insulin in older people aged 70 or over - Mayara Sousa Vianna; Patrícia Aparecida Barbosa Silva; Cíntia Vieira do Nascimento; Sônia Maria Soares (Universidade de São Paulo, 2017)
ABSTRACT Objective: to analyze the self-care competence in the administration of insulin performed by older people aged 70 or over. Method: cross-sectional study carried out with 148 older people aged 70 or over, who performed self-administration of insulin. Data collection was carried out using a structured questionnaire and an adapted guide for the application of the Scale to Identify Self-Care Competence of Patients with Diabetes, at the participants' home. Data analysis included descriptive and inferential statistical tests, with forward logistic regression. Results: the prevalence of self-care competence in the administration of insulin was 35.1%. Handwashing error was the most frequent in self-administration of insulin. Self-care competence was negatively associated with retirees and positively associated with senior patients who performed capillary blood glucose monitoring and skin pinching during insulin application. Conclusion: there was low self-care competence and it was associated with both the sociodemographic and the clinical characteristics with regard to self-application of insulin by the older people.